(untitled) (ACME, 2020)
The paper deals with the study of tomb 24 from the Ca’ Morta cemetery (Como). The tomb was discovered in late December 1958 near the Gini quarry, in the southernmost part of the Ca’ Morta cemetery. The collation of the sources – excavation diary, letters to the Archaeological Superintendence, preliminary publication (RAC 1958) and publication by F. Rittatore (1966) – made it possible to detect that some materials are currently missing. The paper presents a complete catalogue of all the materials currently kept at the archaeological museum P. Giovio di Como. After a brief survey of the history of research on the chronological articulation of the Golasecca culture, the Author proceeds to the typological and chronological study of the pottery and of the bronze sheet cup, of the fibulae, and other objects found inside the urn. The analysis of the burnt bones attributes the tomb to an adult female and this has been confirmed by the grave-goods: the boat-shaped fibulae, the fibulae with amber decorated bow, the openwork pendants (so-called pomegranate pendants), the stop-folds discs and earrings in bronze sheet are all characteristic elements of the female costume. From a chronological point of view, on one hand there are some elements of continuity with phase Golasecca I C, on the other there are more elements of novelty that allow to date the tomb to the beginning of Golasecca II period (phase G. II A).